2022
DOI: 10.1038/s41467-022-31561-4
|View full text |Cite
|
Sign up to set email alerts
|

Bixbyite-type Ln2O3 as promoters of metallic Ni for alkaline electrocatalytic hydrogen evolution

Abstract: The active-site density, intrinsic activity, and durability of Ni-based catalysts are critical to their application in industrial alkaline water electrolysis. This work develops a kind of promoters, the bixbyite-type lanthanide metal sesquioxides (Ln2O3), which can be implanted into metallic Ni by selective high-temperature reduction to achieve highly efficient Ni/Ln2O3 hybrid electrocatalysts toward hydrogen evolution reaction. The screened Ni/Yb2O3 catalyst shows the low overpotential (20.0 mV at 10 mA cm−2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
60
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 112 publications
(61 citation statements)
references
References 70 publications
1
60
0
Order By: Relevance
“…The Tafel slopes of R-NF-Pt is 49.7 mV dec −1 (Figure 5b), which is lower than those of Pt NPs (78.8 mV dec −1 ), and Pt/C (58.5 mV dec −1 ), indicating that the NiO x -O V coupling will facilitate the sluggish water dissociation process of HER on Pt NPs. [58,59] It was reported that the OH ad -M interaction is an important descriptor determining the HER activity. [60] The strong OH ad M binding could accelerate the adsorption of water molecules and cleaving of HOH bond.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Tafel slopes of R-NF-Pt is 49.7 mV dec −1 (Figure 5b), which is lower than those of Pt NPs (78.8 mV dec −1 ), and Pt/C (58.5 mV dec −1 ), indicating that the NiO x -O V coupling will facilitate the sluggish water dissociation process of HER on Pt NPs. [58,59] It was reported that the OH ad -M interaction is an important descriptor determining the HER activity. [60] The strong OH ad M binding could accelerate the adsorption of water molecules and cleaving of HOH bond.…”
Section: Resultsmentioning
confidence: 99%
“…[60] The strong OH ad M binding could accelerate the adsorption of water molecules and cleaving of HOH bond. [59,60] Then we measured the CV curves to observe the OH adsorption and desorption behavior (OH ad region is usually in the range of ≈0.6-0.95 V) on the surfaces of R-NF-Pt and Pt/C electrodes. As shown in Figure S18 (Supporting Information), R-NF-Pt shows an obvious negative shift of OH adsorption peak compared with that of Pt/C, revealing the stronger OHbinding on the surface of R-NF-Pt, [59] which is consistent with the DFT result (Figure 4a).…”
Section: Resultsmentioning
confidence: 99%
“…It is worth noting that the surface of TCNF was coated with bark-like amorphous components, which are considered to be amorphous TiO 2-x and will be discussed below (Figure S2d, Supporting Information). From the SEM and TEM images (Figure 1b-d corresponding to the (111) and (200) lattice plane was surrounded by several graphitic carbon layers, [42,43] which is confirmed by the HRTEM image in Figure 1e and Figure S3c,d 1g). To further confirm the composition of titanium oxide, the synthesis temperature of NTCNF was raised to 700 °C and labeled as NTCNF-700.…”
Section: Resultsmentioning
confidence: 54%
“…These 3D interconnected rough CNFs accompanied by a uniform distribution of nickel particles are favorable for the formation of NiS bonds during the reduction process of LiPSs to accelerate the nucleation of Li 2 S/Li 2 S 2 . The single‐crystalline Ni nanocrystalline corresponding to the (111) and (200) lattice plane was surrounded by several graphitic carbon layers, [ 42,43 ] which is confirmed by the HRTEM image in Figure 1e and Figure S3c,d, Supporting Information. Similarly, in Figure 1f, in addition to the lattice fringes corresponding to the (111) and (200) lattice plane of Ni nanoparticle, there is also a flocculent dark area connected with it, which is amorphous TiO 2‐ x .…”
Section: Resultsmentioning
confidence: 79%
“…28 Hydrogen (H 2 ) is a clean, carbon-free energy carrier and a promising alternative for solving energy supply problems in the future. 29,30 The rational and efficient use of hydrogen energy is one of the most pressing issues today. Continuous production of high-purity hydrogen by electrochemical water splitting is a particularly attractive route, but requires efficient and stable electrocatalysts to drive the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) in the water splitting process.…”
Section: Mof-based Electrocatalysts For the Hydrogen Evolution Reactionmentioning
confidence: 99%